Editorial: Development of study programmes - Karl-Heinz Gerholz; Dieter Euler; Peter F. E. Sloane (Forum Neue Medien in der Lehre Austria, 2014)
21.03.2014 | Karl-Heinz Gerholz (Paderborn), Dieter Euler (St. Gallen) & Peter F. E. Sloane (Paderborn)